The Handbook of Portuguese linguistics - Wetzels, Leo; Costa, João 1972-; Menuzzi, Sergio 1964- (Wiley Blackwell, 2020)
The handbook of Portuguese linguistics presents a comprehensive overview of research within the Brazilian and European variants of the Portuguese language. It includes chapters focusing on the key areas of linguistic study, including phonetics, phonology, morphology, syntax, semantics, pragmatics, linguistic change, language variation and contact, and acquisition. Essential reference work for scholars of Portuguese linguistics and Romance languages. Chapters written by an international team of research specialists highlight both the consensus and the controversies within the various subfields of Portuguese linguistics. Examines Portuguese linguistics in relation to syntax, phonology, morphology, semantics/pragmatics, acquisition, and sociolinguistics. Written in an accessible overview style and designed for advanced students and current scholars in the field alike"--Provided by publisher.